Balanced scorecard implementation within a Malaysian government-linked company / Norlaila Md Zin …[et al.] - Md Zin, Norlaila; Sulaiman, Suzana; Ramli, Aliza; Nawawi, Anuar (Universiti Teknologi MARA Cawangan Selangor, 2012)
This study attempts to gain insights on the implementation of Balanced Scorecard (BSC) within a Malaysian Government-linked Company (GLC) in line with the government-led GLC Transformation Programme (GLCTP). The GLCTP was introduced by the Malaysian Government to steer the GLCs in becoming regional and international players. The study employs a case study method involving semi-structured interviews, review of documentation and website information. Consistent with the literature, our findings revealed that the case firm indeed implements BSC that has been tailored to its own needs. In this paper, we also suggest that four key factors: top management commitment, information technology (IT), communication, and organisational culture are critically required for GLC firms to successfully implement the BSC.